Hubungan Terpaan Berita COVID-19 di Industri Penerbangan Pada Media Online dan Tingkat Kecemasan Tertular COVID-19 dengan Pengambilan Keputusan Menggunakan Jasa Transportasi Udara Masa New-Normal - Widya K. Siahaan; Joyo Nur Suryanto Gono; Agus Naryoso (Interaksi Online, 2021)
Before making a decision, the individual needs related information. Online media becomes the fastest means of finding information. In addition to cognitive aspects, individual affectives are also influential in the decision-making process. This study aims to find out the relationship between the exposure of COVID-19 news in the aviation industry in online media and the level of anxiety of contracting COVID-19 with decision making using new-normal air transportation services. Use the Theory of Persuasion "Drive Model" and Theory of Emotions to explain the correlation between variables. Non-random sampling technique by purposive sampling. The sample was studied by 50 people, with the criteria of air transportation service users during the new-normal, aged 18-55 years and had been hit by news of COVID-19 transmission in the aviation industry from online media. Kendall tau-b hypothesis test shows a value of 0.509 meaning that there is no relationship between COVID-19 news exposure and decision making using air transportation services, while the level of anxiety of contracting COVID-19 is closely related to decision making using air transportation services with a significance value of 0.000. Through these findings, it is recommended that health protocols be improved again by tightening flight requirements/rules and the public is more aware of the compliance of health protocols and reducing mobility of travel to minimize transmission of COVID-19 transmission